A decentralised point-of-care testing model to address inequities in the COVID-19 response. Issue 7 (July 2021) - Hengel, Belinda; Causer, Louise; Matthews, Susan; Smith, Kirsty; Andrewartha, Kelly; Badman, Steven; Spaeth, Brooke; Tangey, Annie; Cunningham, Phillip; Saha, Amit; Phillips, Emily; Ward, James; et al.
Summary: The COVID-19 pandemic is growing rapidly, with over 37 million cases and more than 1 million deaths reported by mid-October, 2020, with true numbers likely to be much higher in the many countries with low testing rates. Many communities are highly vulnerable to the devastating effects of COVID-19 because of overcrowding in domestic settings, high burden of comorbidities, and scarce access to health care. Access to testing is crucial to globally recommended control strategies, but many communities do not have adequate access to timely laboratory services. Geographic dispersion of small populations across islands and other rural and remote settings presents a key barrier to testing access. In this Personal View, we describe a model for the implementation of decentralised COVID-19 point-of-care testing in remote locations by use of the GeneXpert platform, which has been successfully scaled up in remote Aboriginal and Torres Strait Islander communities across Australia. Implementation of the decentralised point-of-care testing model should be considered for communities in need, especially those that are undertested and socially vulnerable. The decentralised testing model should be part of the core global response towards suppressing COVID-19.